2021
DOI: 10.1155/2021/1328444
|View full text |Cite
|
Sign up to set email alerts
|

ZC3H13 Inhibits the Progression of Hepatocellular Carcinoma through m6A-PKM2-Mediated Glycolysis and Enhances Chemosensitivity

Abstract: Objective. N6-Methyladenosine (m6A) is the most prevalent RNA epigenetic modulation in eukaryotic cells, which serves a critical role in diverse physiological processes. Emerging evidences indicate the prognostic significance of m6A regulator ZC3H13 in hepatocellular carcinoma (HCC). Herein, this study was conducted for revealing biological functions and mechanisms of ZC3H13 in HCC. Methods. Expression of ZC3H13 was examined in collected HCC and normal tissues, and its prognostic significance was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…ZC3H13 , an m6A methyltransferase, also plays an important role in tumors ( Wang et al, 2020 ; Song et al, 2022 ). In breast cancer ( Gong et al, 2020 ) and colorectal cancer ( Zhu et al, 2019 ), ZC3H13 plays a tumor suppressive role, while in hepatocellular carcinoma, ZC3H13 promotes the malignant behavior of hepatocellular carcinoma cells ( Wang Q. et al, 2021 ). CD74 , a key molecule involved in antigen presentation, B-cell differentiation and inflammatory signaling, could be considered as a new candidate target and vaccine for tumor immunotherapy to combat tumors ( Stein et al, 2007 ; Borghese and Clanchy, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…ZC3H13 , an m6A methyltransferase, also plays an important role in tumors ( Wang et al, 2020 ; Song et al, 2022 ). In breast cancer ( Gong et al, 2020 ) and colorectal cancer ( Zhu et al, 2019 ), ZC3H13 plays a tumor suppressive role, while in hepatocellular carcinoma, ZC3H13 promotes the malignant behavior of hepatocellular carcinoma cells ( Wang Q. et al, 2021 ). CD74 , a key molecule involved in antigen presentation, B-cell differentiation and inflammatory signaling, could be considered as a new candidate target and vaccine for tumor immunotherapy to combat tumors ( Stein et al, 2007 ; Borghese and Clanchy, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its upregulation in cholangiocarcinoma and EC ( Guo et al, 2021 ), we found that ZC3H13 acts as a tumor suppressor in HCC, consistent with the findings in breast and ovarian cancer ( Zhang et al, 2020b ; Wang et al, 2021a ), suggesting functional diversity of ZC3H13 in different tumors. Very recently, an independent study indicated that ZC3H13 suppressed the progression of HCC through m 6 A-PKM2-mediated glycolysis and sensitized HCC cells to cisplatin, which offered a novel insight into ZC3H13 downregulation in HCC ( Wang et al, 2021b ). Moreover, another study on colorectal cancer found that ZC3H13 inhibits tumor cell proliferation and invasion by downregulating the expression of Snail, cyclin D1 and cyclin E1 by inhibiting the RAS signaling pathway ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA mir4458hG, along with IGF2BP2, upregulates HK2 and GLUT1 expression to upregulate glucose metabolism in HCC 366 . In contrast, the m 6 A methyltransferase ZC3H13 impairs PKM2 mRNA stability, thereby attenuating glycolysis and improving the susceptibility of HCC cells to cisplatin 367 . And investigation of clinical human samples has revealed that the m 6 A demethylase ALKBH5 upregulates the expression of ubiquitin protein ligase E3 component N‐recognin 7 (UBR7), which is a negative regulator of glycolysis, and activates the kelch‐like ECH‐associated protein 1 (Keap1)/nuclear factor erythroid 2‐related factor 2 (Nrf2)/BTB domain and CNC homolog 1(Bach1)/HK2 pathway, thereby attenuating aerobic glycolysis in HCC 368 .…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“… 366 In contrast, the m 6 A methyltransferase ZC3H13 impairs PKM2 mRNA stability, thereby attenuating glycolysis and improving the susceptibility of HCC cells to cisplatin. 367 And investigation of clinical human samples has revealed that the m 6 A demethylase ALKBH5 upregulates the expression of ubiquitin protein ligase E3 component N‐recognin 7 (UBR7), which is a negative regulator of glycolysis, and activates the kelch‐like ECH‐associated protein 1 (Keap1)/nuclear factor erythroid 2‐related factor 2 (Nrf2)/BTB domain and CNC homolog 1(Bach1)/HK2 pathway, thereby attenuating aerobic glycolysis in HCC. 368 METTL14 has also been reported to upregulate the expression of the ubiquitin‐specific peptidase 48 (USP48) and the histone deacetylase sirtuins (SIRT6), thereby performing a suppressive function in the metabolic reprogramming of HCC cells.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%